Hubungan pulangan saham dengan faktor fundamental: ujian menggunakan model berbilang faktor - Abdul Manaf Hussin (Penerbit Universiti Kebangsaan Malaysia, 2001)
The purpose of this study is to examine the relationship between average stock return and 10 firm's specific factors: Debt-Asset Ratio (D/A), Debt-Equity Ration (D/E), Book Equity-Market Equity Ratio (B/M), Dividend Yield (DY), Pay Out Ratio (POR), Price-Earning Ratio (P/E), Earning Per Share (EPS), Earning Growth (EG), Asset Growth (AG) and Market Capitalisation (MVE) in Kuala Lumpur Stock Exchange (KLSE). This study utilised 160 stock selected from companies continuously listed on the main board of KLSE from the period January 1988 through December 1998. The test in this study was divided into two main sections. To examine the relationship between stock return with beta and 10 fundamental factors, Multiple-Factor Model (MBF) and two regression statistics: 1) Ordinary Least Square (OLS) and 2) Seemingly Unrelated Regression (SUR) model, were used. Test results showed that both fundamental and beta, together, were able to capture up to 72.12 percent of the variabililty in stock return, the highest result in that area. The finding of this study indicates that fundamental factors are more powerful in explaining variability of stock's return